Islamic Education Monitoring and Evaluation Management at Al Amanah Junior High School, Cileunyi During Covid 19 Pandemic - Mohamad Erihadiana; R. Rofiani; Harkit Rahmawati; Ade Een Khaeruniah (STAI AL-FALAH CICALENGKA, 2021)
This study intends to analyze the management of supervision and evaluation of education at Al Amanah junior high school Cileunyi during the Covid 19 pandemic. Through a naturalistic qualitative approach, i.e. research conducted by examining problems that are naturally occurring at Al Amanah junior high school Cileunyi, then obtained data showing distance learning process implemented by the school during the Covid 19 pandemic. The process of collecting data via whatsapp and telephone calls,. The results of the study indicate that the management of supervision and evaluation of the implementation of the local content curriculum during the Covid 19 pandemic has not been carried out programmatically. This fact shows that there are problems in terms of management, supervision and evaluation, i.e. the process of observing and measuring the operational activities of the Islamic local content curriculum and the results achieved, compared to the education standards that have been set. This also shows that the supervision process by the supervisors has not been maximized, especially the supervisors from the Ministry of Religion. Another finding from this study is that the management of supervision and evaluation by school leaders during the Covid 19 pandemic has not been implemented to organize Islamic local content learning while students study at home.Keywords: Covid 19, Evaluation, Management, Islamic Local Content, Supervision AbstrakPenelitian ini bermaksud menganalisis manajemen pengawasan dan evaluasi pendidikan di SMP Al Amanah Cileunyi pada masa pandemi Covid 19. Melalui pendekatan kualitatif naturalistik, yaitu penelitian yang dilakukan dengan mengkaji permasalahan yang secara natural tengah terjadi di SMP Al Amanah Cileunyi, maka diperoleh data-data yang menunjukkan proses pembelajaran jarak jauh yang diberlakukan sekolah selama masa pandemi Covid 19. Proses pengumpulan data melalui whatsapp dan Panggilan telpon,. Hasil penelitian menunjukkan bahwa manajemen pengawasan dan evaluasi terhadap pelaksanaan kurikulum muatan lokal selama masa pandemi Covid 19 belum dilaksanakan secara terprogram. Kenyataan tersebut menunjukkan adanya persoalan dalam hal manajemen pengawasan dan evaluasi, yaitu belum berjalannya proses pengamatan dan pengukuran terhadap operasional kurikulum muatan lokal islami dan hasil dicapai, dibandingkan dengan standar Pendidikan yang telah ditetapkan. Hal tersebut juga menunjukkan belum maksimalnya proses supervisi oleh Pengawas, khususnya Pengawas dari Kementerian Agama. Temuan lain dari penelitian ini adalah belum berjalannya manajemen pengawasan dan evaluasi oleh pimpinan sekolah selama masa pandemi Covid 19 yang dibuat untuk menyelenggarakan pembelajaran muatan lokal islami selama peserta didik belajar di rumah.Kata Kunci: Covid 19, Evaluasi, Manajemen, Muatan Lokal Islami, Supervisi